The world of goods : towards and anthropology of consumption - Douglas, Mary (Routledge, 2002)
In this work, a leading anthropologist and an economist join forces to suggest - what market researchers have long suspected and anthropologists have observed firsthand in other cultures - that people use goods as a means of communicating with each other. Food, for example, is not just a way of relieving hunger, but is also a means of communicating socially shared meanings - about time (morning or evening, winter or summer), status, the quality of social encounters (festive or everyday), and much else besides. The same is true of most other goods: the clothes we wear, the homes we live in, the cars we drive - all are culturally determined means for communicating socially shared meanings about ourselves. This text shows precisely how the insights of anthropology can help us better understand the varied ways in which we use the "world of goods" to communicate.